Sankcje podatkowe jako instrument presji ekonomicznej wobec Federacji Rosyjskiej w kontekście wojny w Ukrainie - Lipniewicz, Rafał (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The paper presents legal and economic aspects of tax sanctions imposed by some countries (international organizations) on the Russian Federation in response to this country’s aggression against Ukraine in February 2022. The main research question is whether tax restrictions against Russia are fiscally and economically severe enough to make an impact on Russian political and military decisions in the context of the invasion as Moscow’s budget deficit is getting higher. The conducted research shows that due to the symmetry (the mirror effect) of adverse tax consequences (and also economic consequences) associated with the imposition of most of tax sanctions, even countries that strongly support Ukraine in the war have not decided to adapt such restrictive measures against the Russian Federation that could significantly affect fiscal situation in Russia and, above all, reduce tax benefits resulting from international tax treaties, which still apply to Russian taxpayers who conduct cross-border business activity and invest abroad.
Keywords: sankcje ekonomiczne; Rosja; Ukraina; współpraca podatkowa; wymiana informacji; dochód zagraniczny